Disordered rock salt materials and methods of forming same

By adding elements such as fluorine, phosphorus and sulfur to the disordered rock salt structure, the improved disordered rock salt composition is solved, and the problems of short cycle life and insufficient safety of lithium-ion batteries are achieved, and a longer life and safer battery is achieved performance.

CN119256406APending Publication Date: 2025-01-03WILDCAT DISCOVERY TECHNOLOGIES INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380042003.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-03
Filing Date
2023-06-01
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing disordered rock salt structure lithium-ion batteries have short cycle life and insufficient safety, making it difficult to meet the needs of longer life and safer battery.

Method used

By adding elements such as fluorine (F), phosphorus (P), sulfur (S) and nitrogen (N) to the disordered rock salt structure, an improved disordered rock salt (DRS) composition is formed to replace some oxygen atoms and improve the battery's Cycle life and safety.

Benefits of technology

The DRS composition significantly extends the long-term cycle life of the battery and makes the battery safer by reducing the oxygen redox voltage and avoiding the electrolyte oxidation during charging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119256406A_ABST
    Figure CN119256406A_ABST
Patent Text Reader

Abstract

A disordered rock salt (DRS) with improved properties has cations consisting of lithium and one other metal and anions consisting of oxygen and fluorine and one or more of phosphorus, sulfur and nitrogen. The substitution of one or more of P, S, and N at the oxyanion site may achieve improved battery cycle life and / or may be used to fabricate safer batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries. Background Art

[0002] Lithium metal oxides have been used to formulate cathode materials for lithium-ion batteries. The cathodes are derived from several basic crystal structure types, such as spinel, olivine, and layered oxide structures. Layered oxide structures include lithium-excess type structures, in which extra lithium is present in the structure.

[0003] Recently, attention has focused on disordered rock salt structures, such as those formed from certain lithium metal oxides. A compound represented by the formula:

[0004]

[0005] Where M is a divalent or trivalent cation, it has been shown to be a promising class of transition metal oxides for use as cathodes in lithium-ion batteries. Compounds of formula (1) are considered to be disordered rock salts in which random atomic arrangements of lithium and transition metal ions are stacked in a close-packed cubic structure. These disordered rock salt compositions offer the ability to contain up to 3 lithium atoms per molecular formula unit, which is more than conventional excess lithium layered materials. Formula (1) can be converted and represented as Li x M y N z O w .

[0006] Disordered rock salt structures are attractive cathode materials for next-generation lithium-ion batteries because they have higher specific energy density (e.g., higher theoretical energy density) than state-of-the-art cathode materials such as layered lithium metal oxide structures. For example, the theoretical gravimetric energy density of some disordered rock salt structure materials is about 1120 Wh / kg, while the theoretical gravimetric energy density of LiMn2O4 active materials is about 492 Wh / kg, and LiMn 1.5 Ni 0.5 The theoretical gravimetric energy density of O4 is about 691 Wh / kg. This energy density is particularly attractive when using lower cost raw materials as components of the disordered rock salt structure (such as manganese). Therefore, disordered rock salt materials can achieve relatively high energy density at relatively low material cost. In order to achieve comparable energy density, known cathode materials require higher cost raw materials, such as cobalt or nickel.

[0007] The cycle life of disordered rock salt materials tends to be shorter than that of existing lithium ion batteries. Recently, attempts to improve the cycle life of disordered rock salt batteries by replacing some of the oxygen with fluorine have been described, such as described in U.S. Patent No. 10,280,092. Nevertheless, it is still desirable to provide a battery composed of a disordered rock salt cathode that has a longer life and other desirable attributes, such as a safer battery. Summary of the invention

[0008] We have discovered improved disordered rock salt (DRS). DRS can exhibit longer long-term cycle life. DRS can exhibit a lower oxygen redox voltage, which in turn can make the battery safer (exhibiting a lower charging voltage platform on the oxygen redox platform). The advantage of the lower charging voltage of the platform is that the battery electrolyte is exposed to an environment that is less likely to cause its oxidation. It has been found that the addition of F and any one or all of P, S and N produces the above-mentioned desired properties while maintaining the same initial capacity, but with improved life and other properties. Each of these substances replaces some oxygen (anions) in the disordered rock salt structure. In DRS, most of the anions are oxygen, and the rest are composed of F, P, S and N as described above (O substitution). The ratio of F / (P, S and N) can be any useful, but it is desirable to be 1 or greater than 100, 50, 25, 20 or 15 in moles. The combination of F with any one of P, S, and N improves one or more properties, which may be different. That is, P, S and N can be used alone or in combination, depending on the desired one or more properties.

[0009] As used herein, when a majority of a component is specified, it means more than 50 mole % or (as will be readily understood from the context used) to substantially all of the component (99% or less). That is, a majority of a particular component of a component is present in an amount greater than 50% to 99%, 90%, 80%, 70% or 60% of the component. When a minority of a component is a specified component, it is present in an amount less than 50% to about 1%, with the remainder being the majority of the specified components.

[0010] The composition comprises a disordered rock salt having cations consisting of lithium and at least one other metal and anions consisting of one or more of oxygen, fluorine and phosphorus, sulfur and nitrogen. Ideally, oxygen accounts for the majority of the anions, with a minority consisting of F and one or more of P, S and N. Fluorine is the majority of two or more of F, S, P and N. Exemplarily, it is desirable that the F / (P, S and N) ratio is at least 1 to 100, 50, 25, 10, 5 or 2.

[0011] DRS can be used in primary and secondary battery lithium ion batteries.DRS can be used with any suitable electrolyte, separator and anode (such as those known in the art). BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 The X-ray diffraction pattern of the disordered rock salt of the present invention and the X-ray diffraction pattern of the disordered rock salt not of the present invention are shown.

[0013] Figure 2 The first cycle capacity and coulombic efficiency of the half-cell of the disordered rock salt of the present invention and the disordered rock salt of not the present invention are shown.

[0014] Figure 3-5 The first cycle capacity and (dQ / dV) graphs are shown for a battery having a disordered rock salt cathode of the present invention and a cathode having a disordered rock salt cathode not of the present invention.

[0015] Figure 6-8 The capacity of a battery according to the invention and a battery not according to the invention is shown versus the number of cycles. DETAILED DESCRIPTION

[0016] The following definitions apply to some aspects described with respect to some embodiments of the present invention. These definitions may also be expanded upon herein. Each term is further explained and illustrated by the description, drawings, and examples. Any interpretation of the terms in this specification should take into account the complete description, diagrams, and examples provided herein.

[0017] The singular terms "a", "an" and "the" include plural references unless the context clearly dictates otherwise. Thus, for example, reference to one item may include plural items unless the context clearly dictates otherwise.

[0018] Rate "C" means (depending on the context) a fraction or multiple of the discharge current relative to the "1 C" current value (at which the battery (in a substantially fully charged state) will be substantially fully discharged in one hour), or a fraction or multiple of the charge current relative to the "1 C" current value (at which the battery (in a substantially fully discharged state) will be substantially fully charged in one hour).

[0019] To the extent that certain battery characteristics vary with temperature, those characteristics are specified at 30 degrees Celsius unless the context clearly dictates otherwise.

[0020] Ranges presented herein include their endpoints. Thus, for example, a range of 1 to 3 includes the values ​​1 and 3 and intermediate values.

[0021] DRS compositions and morphologies (e.g., structures) can be used to formulate electrodes of electrochemical cells. More specifically, DRS can be used to form cathodes. Lithium-ion batteries include an electrolyte formulation in which the concentration of a lithium salt is suitable for conducting lithium ions between the cathode and the anode through the electrolyte formulation during discharge and charge operations.

[0022] In disordered rock salt, both lithium and transition metals occupy a cubic close-packed lattice of octahedral sites. In electrochemical reactions, lithium diffusion occurs by lithium jumping from one octahedral site to another via an intermediate tetrahedral site. The lithium in the intermediate tetrahedral site is the activated state in lithium diffusion. The activated tetrahedral lithium ion shares faces with the following four octahedral sites: (i) a site previously occupied by the lithium ion itself; (ii) a vacant site that the lithium ion will enter; and (iii and iv) two sites that can be occupied by lithium, a transition metal, or a vacancy.

[0023] The composition may be a disordered rock salt (DR) comprising a substance having the formula:

[0024] Li x M' y M z O 2-(a+b) F a Z b

[0025] Of which 1.0 <x<1.75;0≤y<0.55;0.1<z<1;0≤(a+b)<0.7;(b> 0) M' is one of Ti, Ta, Zr, W, Nb or Mo; M is one or more of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh, Sn, Bi and Sb; Z is one or more of P, N and S. Other dopants may also be included, such as dopants that replace Li, such as Na and Mg, which may be in any useful amount, but generally up to about 10 mol% or 5 mol% to 0.01 mol% of such dopants present in the lithium and DR.

[0026] The amount of F and Z can be the majority or minority of the anions (i.e., O, F, and one or more of P, S, and N). Illustratively (a+b) is 0.05 to 1.5, 1, 0.95, 0.8, 0.65, 0.5. It may be desirable for a to be 0.05 to 0.25. Z can be any combination of P, N, S, or just one of them. When there are two or more, the ratio between P, N, and S can be any useful ratio, depending on the properties sought. For example, when it is necessary to reduce the redox potential, S may need to be present. It may also be desirable for S to account for the majority of P, S, and N present in the composition.

[0027] The composition can have any desired Li of 1 or more, but it is desired that the Li represented by x is at least 1.1, 1.15, 1.2 to 1.65, 1.5, or 1.4.

[0028] The cations of the composition can be the metals described, but ideally, at least one metal represented by M is composed of one or more of Ti, Mn, Fe, Co, V, Cr, Ni, and Cu. It may be desirable that M is composed of Ti and Mn. The composition may illustratively be a composition in which M' is composed of Nb. When Nb is present, it may be desirable that M is composed of Mn. Exemplarily, M' may be Nb and M may be Mn. When Nb and Mn are present with or without other metals, they may be present in a Mn / Nb ratio of 1 or 2 to 200, 150, 100, 75, 50, 25, or 10 by mole.

[0029] DRS can be made by any suitable method such as methods known in the art for making disordered rock salts. Exemplary methods are described in U.S. Pat. Nos. 10,280,092, 10,978,706, and ACS Appl Mater Interfaces. 2019 Oct 2; 11(39):35777-35787, each of which is incorporated herein by reference.

[0030] For example, DRS is desirably composed of micron-sized clusters or aggregates of submicron-sized particles, which can be used to increase the capacity and energy density of the battery cathode. Micron-sized clusters are also referred to herein as secondary particles. Secondary particles desirably have an average particle size (e.g., diameter) of micrometer scale, such as between 1 micrometer and 20 micrometers. Submicron-sized particles aggregate to form secondary particles. Submicron-sized particles are also referred to herein as primary particles. The terms "primary" and "secondary" indicate that primary particles are formed prior to secondary particles, and secondary particles are aggregates of primary particles. Primary particles have an average particle size (e.g., diameter) of nanometer scale, such as less than 400 nanometers. Submicron primary particles of disordered rock salt material can provide desired conductivity, while micron-sized secondary particles of disordered rock salt material produce high electrode energy density.

[0031] In order to form micron-sized clusters, the precursor suspension can be ground to form a mixture of primary particles in the suspension. The precursor includes a metal compound and is selected based on the desired composition of the DRS material. One or more precursors can be compounds (e.g., metal compounds) composed of oxygen, fluorine and one or more P, S and N, such as oxides, hydroxides, nitrogen oxides, nitrides, nitrates, sulfides, sulfates, sulfites, phosphates, phosphites, fluorides and combinations thereof. Examples of precursors can include Mn2O3, LiOH, Nb2O5, LiF, NbF5 and / or the like. In order to dope oxygen sites with one or more of P, S and N, at least one precursor includes one of these elements. Possible P, S and N precursors can include elements P, S or N, metal nitrides (e.g., lithium nitride), metal nitrates, metal nitrites, metal phosphates, metal phosphides, metal phosphites, metal sulfites, metal sulfates, metal sulfides (e.g., lithium sulfide), wherein the metal is a desired metal and a combination thereof in DRS.

[0032] The precursor can be mixed in a liquid such as water to make a suspension in the desired amount to achieve the desired DRS stoichiometry. Grinding can be carried out by any method that can be used to achieve the desired particle size, such as a micro-media mill, a ball mill, a planetary mill or a grinding mill. The average particle size of the primary particles can be up to 2 microns, 1 micron, 400 nanometers (nm), 200 nm or 100 nm. For example, the average particle size can be no greater than 50 nm, 40 nm, 30 nm, 20 nm, etc. An example of a suitable micro-bead mill is a Buhler PML2 mill (Buhler Group).

[0033] The suspension of precursor particles may then be dried by any suitable method such as spray drying to form secondary particles. Spray drying may be performed using any known commercially available spray dryer, such as a micro spray dryer such as the Buchi model B-290.

[0034] The spray dried precursor particles can then be heated to an annealing temperature. The annealing temperature causes the precursors in the secondary particles to react and form a single phase. Ideally, the temperature and time are such that the resulting DRS retains the micron-sized spray dried secondary particle morphology. The annealing temperature can be 500°C, 750°C to 900°C, 1000°C or 1200°C for a duration of 10 minutes, 1 hour, 2 hours, 3 hours or 5 hours to 12 hours or 24 hours.

[0035] The annealing process can be carried out under any suitable atmosphere, and the atmosphere can be static or flowing. The annealing environment can be under rare gas, nitrogen, atmosphere or dry air and combination thereof, to achieve the required partial pressure of one or more gases. In other embodiments, the annealing conditions can be selected based on the composition of the disordered rock salt precursor, such as which metals are present. For example, a composition based on manganese can adopt the above conditions (e.g., 750-900°C, for 6 to 24 hours), while a composition based on another metal can have a wider temperature range, a higher range or a lower range and / or a wider, longer or shorter time period range, or multiple annealing steps.

[0036] In an alternative embodiment, the lithium source may be set aside until the annealing step, rather than grinding and spray drying the lithium-containing precursor with the other precursors. For example, spherical secondary particles may be produced as described above, except that the precursor lacks lithium. They are then mixed with the lithium compound and annealed as described above. Mixing may be performed by any suitable and desired method that minimizes comminution of the spray-dried secondary particles, such as a V-type mixer.

[0037] The DRS phase can be formed before grinding. For example, the DRS phase can be formed by a solid-state chemical method such as a solid-state redox reaction of an oxide ion, which can be formed by grinding of a precursor. The formed DRS phase can be ground, then spray-dried, and other additives such as carbon can be added. One or more carbon precursors can include acetylene black, carbon black, carbon fiber, graphite, carbon nanotubes, KJ600 and / or the like. One or more carbon precursors can be ground according to a ratio in which disordered rock salt powder accounts for the majority and carbon precursor accounts for the minority. For example, the ratio of DRS powder to carbon precursor can be 60:40 to 99:1.

[0038] DRS can be used to form a cathode by any suitable method such as methods known in the art. For example, DRS powder can be mixed with a binder such as a polymer (for example, polyfluoropolymers such as polyvinylidene fluoride) and one or more solvents that can be used to make a cathode to form a slurry. Non-limiting examples of one or more solvents can be aprotic polar solvents, such as methyl-2-pyrrolidone (NMP). The slurry can then be deposited on a metal current collector (such as stainless steel, copper or any suitable conductive metal foil), and the solvent is removed to form a cathode.

[0039] Ideally, the DRS of the cathode has an average secondary particle size of at least 1 to 20 microns. Each secondary particle is an aggregate of primary particles. The DRS primary particles desirably have an average particle size as described herein and may contain other potentially useful particles, such as increasing conductivity (e.g., carbon or other inorganic high ion conductive particles).

[0040] The DRS cathode can be used in a rechargeable lithium-ion battery cell. The battery cell includes a cathode, an anode, a separator, and an electrolyte. The battery or battery cell can be formed in any suitable atmosphere, such as atmospheres common in the art. For example, a high purity argon atmosphere can be used to limit any undesirable contamination from substances present in the atmosphere.

[0041] Example

[0042] Example 1. A composition comprising a disordered rock salt having cations consisting of lithium and at least one other metal and anions consisting of oxygen and fluorine and one or more of phosphorus, sulfur and nitrogen.

[0043] Example 2. The composition of Example 1, wherein oxygen constitutes a majority of the anions.

[0044] Example 3. The composition of Example 2, wherein fluorine comprises a majority of fluorine and one or more of phosphorus, sulfur, and nitrogen.

[0045] Example 4. The composition of Example 1, wherein F / (P, S, and N) is from 1 to 25 on a molar basis.

[0046] Example 5. The composition of Example 1, wherein the disordered rock salt is represented by

[0047] Li x M' y M z O 2-(a+b) F a Z b

[0048] Of which 1.0 <x<1.75;0≤y<0.55;0.1<z<1;0≤(a+b)<0.7;(b> 0) M' is one of Ti, Ta, Zr, W, Nb or Mo; M is one or more of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh and Sb; and Z is one or more of P, N and S.

[0049] Example 6. The composition of Example 5, wherein (a+b) is from 0.05 to 1.5.

[0050] Example 7. The composition of Example 6, wherein (a+b) is from 0.05 to 0.95.

[0051] Example 8. The composition of any one of Examples 5 to 7, wherein a is from 0.05 to 0.25.

[0052] Example 9. The composition of any one of Examples 5 to 8, wherein Z is P, N or S.

[0053] Example 10. The composition of any one of Examples 5 to 9, wherein M' is Nb and y is greater than zero.

[0054] Example 11. The composition of any one of Examples 5 to 10, wherein x is from 1.1 to 1.65.

[0055] Example 12. The composition of any one of Examples 5 to 11, wherein x is from 1.15 to 1.5.

[0056] Example 13. The composition of any one of Examples 5 to 12, wherein x is from 1.2 to 1.4.

[0057] Example 14. The composition of any one of Examples 5 to 13, wherein M consists of one or more of Ti, Mn, Fe, Co, V, Cr, Ni, and Cu.

[0058] Example 15. The composition of Example 14, wherein M consists of Ti and Mn.

[0059] Example 16. A cathode of a rechargeable battery, the cathode comprising disordered rock salt powder having cations consisting of lithium and one other metal and anions consisting of oxygen and fluorine and one or more of phosphorus, sulfur and nitrogen.

[0060] Example 17. The cathode of Example 16, wherein the disordered rock salt powder is represented by the following formula:

[0061] Li x M' y M z O 2-(a+b) F a Z b

[0062] Of which 1.0 <x<1.75;0≤y<0.55;0.1<z<1;0≤(a+b)<0.7;(b> 0) M' is one of Ti, Ta, Zr, W, Nb or Mo; M is one or more of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh and Sb; and Z is one or more of P, N and S.

[0063] Example 18. The cathode of Example 16 or 17, wherein the anion redox voltage of the cathode is reduced compared to a disordered rock salt cathode without P, ​​S or N.

[0064] Example 19. The cathode of Example 17, wherein at least some portion of Z consists of S.

[0065] Example 20. The cathode of Example 19, wherein Z consists of S only.

[0066] Example 21. The cathode of any of Examples 17 to 20, wherein M' consists of Nb and M consists of Mn.

[0067] Example 22. The cathode of Example 21, wherein Mn / Nb is 1 to 10 on a molar basis.

[0068] Example 23. The cathode of Example 22, wherein Mn / Nb is 2 to 5 on a molar basis.

[0069] Example 24. A lithium ion battery comprising the cathode of any one of Examples 16 to 23.

[0070] Example 25. The cathode of Example 16, wherein y is greater than 0.01.

[0071] Example

[0072] Comparative Example (control):

[0073] The disordered rock salt was synthesized using Mn2O3, Li2CO3, Nb2O5 and LiF precursors in amounts designed to achieve the Li 1.31 Mn 0.4 Nb 0.1 Ti 0.19 O 1.77-x F 0.23 A x Denoted disordered rock salt, where x is zero. The precursors were mixed in deionized water to make a suspension, and the suspension was ground in a planetary ball mill using zirconium oxide media for 5 hours to form a mixture. The mixture was dried at 100°C in air for 12 hours, and then annealed at 800°C for 4 hours and at 900°C for 12 hours under flowing argon to obtain disordered rock salt (DRS). DRS was ground with a carbon precursor (acetylene black, carbon black, carbon fiber, graphite, carbon nanotubes or KJ600) at 93:7 (weight ratio of powder to carbon) to form an active cathode material mixture.

[0074] Example:

[0075] The method for preparing the disordered rock salt of the embodiment is the same as described above, but different dopant precursors are added during the first mixing to replace 0.01 and 0.02 moles (i.e., x is 0.01 or 0.02) of oxygen / fluorine present in the disordered rock salt of the comparative example. Phosphorus, Li3N and Li2S are used as dopant precursors for P, N and S dopants, respectively.

[0076] Half-cells with an area similar to that of a coin-type battery cell were fabricated and electrochemical cycling tests were performed between 1.5 and 4.6 V for the Li anode at 30 °C.

[0077] The battery cells were formed in a glove box filled with high-purity argon (M-Braun, O2 and humidity content <0.1ppm). The cathode was prepared by mixing the active cathode mixture with poly(vinylidene fluoride) (PVDF, Sigma Aldrich) and 1-methyl-2-pyrrolidone (NMP, Sigma Aldrich) and conductive carbon to obtain a ratio of active material: carbon: PVDF = 90:7:3, and depositing the resulting slurry on a stainless steel current collector by pipetting and drying to form a 2 mg / cm 2 Composite cathode film. For the anode, a thin Li foil (about 300 μm, Gotion) was cut into the required size. Each battery cell includes a composite cathode film, a polypropylene separator (Celgard 2400) and a lithium foil anode. An electrolyte (1.0MLiPF6 in EC / EMC (1:2 v / v)) was used, which contained lithium hexafluorophosphate (LiFP6) in a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) with additives (2 wt%). The battery cell was sealed and cycled between 1.5-4.6V at 30°C with a C / 20 formation rate and a C / 3 cycle rate, where 1C = 300 mAh / g.

[0078] The X-ray diffraction of the disordered rock salt of the control and example is as follows Figure 1 shown. Figure 1 The doping level of the example shown corresponds to an amount where x is 0.02. The X-ray image shows a disordered rock salt structure. However, it is worth noting that the phosphorus doped example shows some residual LiF, which suggests that when using phosphorus as a dopant, the formation method may require different conditions to fully react the LiF (e.g., changing the temperature or milling time).

[0079] Figure 2 The first cycle specific capacity and coulombic efficiency of the control and examples doped at x=0.01 and 0.02 are shown. The specific capacity and coulombic efficiency are determined using the half-cell unit described above. The results show that the first cycle specific capacity and coulombic efficiency of the S and N doped examples are essentially the same. The specific capacity drop of the P doped example is attributed to the presence of LiF and the incomplete formation of disordered rock salt.

[0080] Figure 3The first cycle voltage curves and dV / dQ (Q = capacity) of the sulfur-containing control cell and the example cell are shown. The sulfur-doped material exhibits a lower voltage plateau on the oxygen redox plateau. Sulfur can give up electrons more easily, which can provide a more delocalized electron cloud on the oxygen, making it easier to oxidize. The lower charge voltage plateau can be an advantage because the electrolyte does not have to be oxidatively stable. The sulfur-doped material also exhibits a smaller overpotential between charge and discharge (dQ / dV plot), which can give the battery lower impedance and better energy efficiency. The first cycle voltage curves of the N and P doped examples and controls are shown in Figure 1. Figure 4 and Figure 5 shown.

[0081] Compared to the control (F doped only), the N and P doped examples show improved long term cycle life. (See Figure 6-8 ). However, the S-doped samples showed poor cycling performance, which may be related to the greater contribution of oxygen redox capacity. In other words, if more capacity comes from oxygen in the doped material (relative to the control), the cycle life will be shortened. However, since the oxygen redox of the S-doped samples occurs at a lower potential, the cycling performance of the S-doped samples can be improved by reducing the upper voltage cutoff value.

Claims

1. A composition comprising a disordered rock salt having cations consisting of lithium and at least one other metal and anions consisting of oxygen and fluorine and one or more of phosphorus, sulfur and nitrogen.

2. The composition of claim 1, wherein oxygen constitutes the majority of the anions.

3. The composition of claim 2, wherein fluorine comprises a majority of fluorine and one or more of phosphorus, sulfur and nitrogen.

4. The composition of claim 1, wherein F / (P, S and N) is from 1 to 25 on a molar basis.

5. The composition of claim 1, wherein the disordered rock salt is represented by Li x M' y M z O 2-(a+b) F a Z b Of which 1.0 <x<1.75;0≤y<0.55;0.1<z<1;0≤(a+b)<0.7;(b> 0) M' is one of Ti, Ta, Zr, W, Nb or Mo; M is one or more of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh and Sb; and Z is one or more of P, N and S.

6. The composition of claim 5, wherein (a+b) is from 0.05 to 1.

5.

7. The composition of claim 6, wherein (a+b) is from 0.05 to 0.

95.

8. The composition of claim 5, wherein a is from 0.05 to 0.

25.

9. The composition of claim 5, wherein Z is P, N or S.

10. The composition of claim 5, wherein M' is Nb and y is greater than 0.

11. The composition of claim 5, wherein x is from 1.1 to 1.

65.

12. The composition of claim 11, wherein x is from 1.15 to 1.

5.

13. The composition of claim 12, wherein x is from 1.2 to 1.

4.

14. The composition of claim 5, wherein M consists of one or more of Ti, Mn, Fe, Co, V, Cr, Ni and Cu.

15. The composition of claim 14, wherein M consists of Ti and Mn.

16. A cathode of a rechargeable battery, the cathode comprising disordered rock salt powder having cations consisting of lithium and one other metal and anions consisting of oxygen and fluorine and one or more of phosphorus, sulfur and nitrogen.

17. The cathode of claim 16, wherein the disordered rock salt powder is represented by the following formula: Li x M' y M z O 2-(a+b) F a Z b Of which 1.0 <x<1.75;0≤y<0.55;0.1<z<1;0≤(a+b)<0.7;(b> 0) M' is one of Ti, Ta, Zr, W, Nb or Mo; M is one or more of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh and Sb; and Z is one or more of P, N and S.

18. The cathode of claim 16 or 17, wherein the anion redox voltage of the cathode is reduced compared to a disordered rock salt cathode without P, ​​S or N.

19. The cathode of claim 17, wherein at least some portion of Z consists of S.

20. The cathode of claim 19, wherein Z consists only of S.

21. The cathode of any one of claims 17 to 20, wherein M' consists of Nb and M consists of Mn.

22. The cathode of claim 21, wherein Mn / Nb is 1 to 10 on a molar basis.

23. The cathode of claim 22, wherein Mn / Nb is from 2 to 5 on a molar basis.

24. A lithium ion battery comprising the cathode according to any one of claims 16 to 23.